The familial context of children’s creativity: parenting styles and the climate for creativity in parent–child relationship - Jankowska, Dorota Maria; Gralewski, Jacek (Creativity Studies, 2022)
The purpose of this study was to explore the relationship between dimensions of a constructive parenting style, (i.e. parental acceptance and autonomy granting) factors of the climate for creativity in parent–child relationships (encouragement to experience novelty and variety, encouragement of nonconformism, support of perseverance in creative efforts, and encouragement to fantasize), and parents’ visual mental imagery. 313 parents of children between 6 and 12 years of age participated in the study. The results indicated that (a) a constructive parenting style was positively related to three of four factors of the climate for creativity in the parent–child relationships, i.e. encouragement to experience novelty and variety, support of perseverance in creative efforts, and encouragement to fantasize in the parent–child relationship; (b) parents’ level of vividness of mental imagery was positively related with both parental acceptance of child and autonomy support as well as components of climate for creativity in parent–child relationship; (c) mothers scored significantly higher than fathers in exhibiting acceptance of a child; (d) parents’ gender played an important role in the relations between dimensions of constructive parenting style and factors of climate for creativity in parent–child relationships. Findings were discussed in terms of the implications for further research and theory development in the area of family influences on the development of children’s creativity.